A comprehensive pathological and molecular investigation of viral co-infections in ducks in Egypt - Mohamed, Rania I.; Mosad, Samah M.; Ali, Hanaa S.; Albalawi, Wejdan Oudah; Elsamadony, Hanaa A.; Ramzy, Neven M.; Saad, Alaa S.; Fallatah, Deema; Abdel-Hafez, Lina Jamil M.; Albrakati, Ashraf; Elmahallawy, Ehab Kotb (Frontiers in Microbiology, 2025)
IntroductionDuck production in Egypt plays a significant role in the poultry sector. However, viral infections, such as avian influenza virus (AIV), Newcastle disease virus (NDV), and duck hepatitis A virus (DHAV), pose a significant threat to ducks, leading to substantial economic losses. Despite their impact, data on these duck pathogens in Egypt remain limited.MethodsIn this study, 200 samples from various organs were collected from 20 commercial duck farms and pooled into 20 working samples. Samples of brain, liver, spleen, trachea, and lung were analyzed to detect DHAV, NDV, and H5 and H9 AIV using reverse transcriptase polymerase chain reaction (RT-PCR); then, positive samples were subjected for sequencing. Samples from the same organs were also subjected for histopathological examination.ResultsInterestingly, the RT-PCR detected DHAV, NDV, and H9-AIV, and mixed viral infections were confirmed in some farms. The phylogenetic analysis of DHAV 3D gene revealed that both DHAV-1 and DHAV-3 genotypes are circulating in Egyptian duckling with most tested samples containing DHAV-3 genotype, considered the vaccine used in Egypt contains DHAV-1 strain only. All detected NDV strains in this study are clustered in Genotype VII.1.1 with F0 cleavage site (RRQKR ↓ F) of velogenic NDV. On the other hand, our studied H9-AIV strains are aligned in H9.4.1.1 sub-lineage with other Egyptian field and vaccine seed strains. Local Egyptian vaccine seed strains were found closely related to our isolates than imported vaccines. H9.4.1 strains displayed HA0 protein cleavage site motif PARSSR↓GLF of LPAI. All the aligned Egyptian H9-AIV field and local vaccine strains have 168 N, 191H, 197 T, 224 L, and 234 L amino residues, indicating that these viruses had the characteristic of receptor specificity like that of human influenza virus increasing the zoonotic risk of such virus. Histopathologically, animals showed characteristic lesions in various organs coherent to the infection by these mentioned pathogens.ConclusionCollectively, the study provided novel information about viral infections linked to neurological diseases of ducks in Egypt and concluded that local DHAV vaccine needs to be modified to contain both DHAV-1 and DHAV-3 strains.